CFD simulation and optimization of fluid flow distribution inside printed circuit heat exchanger headers. (2nd April 2016) - Pasquier, U.; Chu, W. X.; Zeng, M.; Chen, Y. T.; Wang, Q. W.; Ma, T.
ABSTRACT: Fluid flow distribution is related to the performance of heat exchangers. Gross flow distribution is often linked to conventional headers and thus jeopardizes the thermo-hydraulic performance. The objective of this paper is to design several configurations of printed circuit heat exchanger headers to enhance its flow uniformity while leveraging its etched nature. Four kinds of inlet headers, i.e., trapezoid header, double header with detail of bypass holes, core integrated header with one layer, and core integrated header with multilayers, are compared. It is found that the traditional headers induce poor flow distributions. Based on the flow characteristics in traditional headers, a novel core integrated header with seven merged channels is proposed. The flow nonuniformity of the heat exchanger with this novel inlet and outlet headers is reduced by 91%, but the pressure drop is increased by 114% compared with the baseline configuration, whereas it shows the best heat transfer performance as well due to the improvement of flow uniformity.